2021
DOI: 10.3390/ijerph182010699
|View full text |Cite
|
Sign up to set email alerts
|

How to Promote Low-Carbon Economic Development? A Comprehensive Assessment of Carbon Tax Policy in China

Abstract: Facing the increasingly severe environmental problems, the development of a green and sustainable low-carbon economy has become an international trend. In China, the core issue of low-carbon economic development is effectively resolving the contradiction between the exploitation and utilization of fossil energy and greenhouse gas emissions (mainly carbon emissions). Based on the SAM matrix, we established a static Computable General Equilibrium (CGE) model to simulate the impact of carbon tax policies on energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Recent contributions by Pretis (2022) and Pan et al (2024) delve into the specificities of carbon tax design and its implications for emissions reduction in general. Similarly, there are a range of case studies, including experiences from Sweden and British Columbia, to elucidate the tangible outcomes and challenges associated with carbon taxation (Metcalf, 2019, Andersson, 2019, Liu et al, 2021, Ptak et al, 2024.…”
Section: Carbon Taxationmentioning
confidence: 99%
“…Recent contributions by Pretis (2022) and Pan et al (2024) delve into the specificities of carbon tax design and its implications for emissions reduction in general. Similarly, there are a range of case studies, including experiences from Sweden and British Columbia, to elucidate the tangible outcomes and challenges associated with carbon taxation (Metcalf, 2019, Andersson, 2019, Liu et al, 2021, Ptak et al, 2024.…”
Section: Carbon Taxationmentioning
confidence: 99%
“…Fourth, facilitate an industrial structure optimization and upgrading strategy that suits the reality of the region. Build a deep industrial system covering the whole industrial chain and promote long-term sustainable economic development [58]. Last but not least, properly optimize the energy structure, appropriately reduce energy use with high carbon emission factors, and raise the proportion of clean energy.…”
Section: Sustainable Industrial Development Policymentioning
confidence: 99%
“…In previous studies, revenue recycling policies also have been considered to limit the negative effects of the carbon tax on economic development and welfare. Liu et al (2021) analyzed the carbon tax recycling policies based on the principle of tax neutrality such as reducing residents' personal income tax, the enterprise income tax rate and the enterprise indirect tax rate. They found that these policies can reduce the drawbacks of the carbon tax on economic development and welfare.…”
Section: Effects Of a Carbon Tax In Vietnammentioning
confidence: 99%